Analysis of Alcoholic Beverage Supervision and Control for Minors under Bandung City Regional Regulation Number 10 of 2024 from the Perspective of Siyasah Dusturiyah - Irfan Gumelar Ramadhan; Ending Solehudin; Bobang Noorisnan Pelita (Journal of Indonesian Islamic Studies, 2026)
The circulation and consumption of alcoholic beverages among minors have become a significant public policy issue due to their adverse effects on health, cognitive development, and social order. In response to this problem, the Bandung City Government enacted Bandung City Regional Regulation Number 10 of 2024 concerning the Supervision and Control of Alcoholic Beverages as a legal instrument to regulate distribution, restrict access, and enhance the protection of children. This study aims to analyze the supervision and control mechanisms for alcoholic beverages affecting minors under Bandung City Regional Regulation Number 10 of 2024, identify the supporting and inhibiting factors influencing its implementation, and examine the regulation from the perspective of Siyasah Dusturiyah. This research employs a normative juridical method using a statutory approach, complemented by empirical data collected through interviews and field observations. The data were analyzed qualitatively using descriptive analysis based on legal materials, statutory interpretation, and the principles of fiqh siyasah. The findings reveal that the supervision mechanism has been implemented through age restrictions for consumers, limitations on sales locations, the establishment of a Supervision and Control Team, enforcement by the Civil Service Police Unit (Satpol PP), the application of administrative and criminal sanctions, and community participation. The effectiveness of these measures is supported by a clear legal framework, inter-agency coordination, and public involvement. However, implementation remains constrained by the circulation of illegal alcoholic beverages, limited institutional resources, and inadequate supervision of digital distribution channels. From the perspective of Siyasah Dusturiyah, the regulation reflects the responsibility of ulil amri (legitimate authority) to promote public welfare (maslahah) through the protection of intellect (hifzh al-'aql), life (hifzh al-nafs), and progeny (hifzh al-nasl). The novelty of this study lies in its comprehensive analysis of the implementation of Bandung City Regional Regulation Number 10 of 2024 by integrating the perspectives of Siyasah Dusturiyah and maqashid al-shari'ah with a specific focus on the protection of minors, supported by empirical findings from the field. This study contributes to the development of Siyasah Dusturiyah within the field of Islamic constitutional law while providing practical recommendations for strengthening local government policies on the supervision and control of alcoholic beverages.